(untitled) (Zien Journal of Social Sciences and Humanities, 2022)
This article is dedicated to the personal names in the novels of Dorothy Richardson, which are an integral part of the lexical and grammatical class of a noun, they are a functional language sign that has its own meaning and means by which this meaning can be conveyed. From the point of view of the content plan, i.e. meaning, personal names will be interesting, the content of which is subject to change: enrichment, expansion, which gives them the opportunity to reach a new level – to be recognized and perceived in society.